Chapter 7 'Not in the name of dharma' A judgment of the Supreme Court of Nepal on mass sacrifices at the Gaḍhī Māī Melā - LETIZIA, CHIARA (Taylor & Francis, 2024)
The five-yearly mass animal sacrifice offered at the festival of the goddess Gaḍhī Māī (Gaḍhī Māī Melā) temple in Bariyarpur, Bara District, in southern Nepal, drew local and international attention in 2009, when news and vivid pictures of the slaughter of thousands of animals circulated globally, giving rise to vehement protests from individuals and animal rights associations. In November 2014, three Public Interest Litigation (PIL) petitions against the sacrifices at the Gaḍhī Māī Melā were filed at the Supreme Court of Nepal. In a 52-page judgment published in August 2016 that dealt with these petitions together, the Supreme Court discussed and criticised the practice of animal sacrifice and ordered the Government of Nepal to implement policies that would lead to its eventual discontinuation. This paper is based on the analysis of legal documents and on interviews with the parties. We present the trajectory of this court case from 2014 to 2019, and we focus on the court's decision, its call for social progress in the name of modernity, its reasoning on whether animal sacrifice is a valid expression of Hinduism, its consideration for this practice deeply rooted in Nepali society, and its call to the government to define and ensure the rights and welfare of animals, meeting the aspiration of the activists. The Court's decision lays down principles that are applicable to sacrifices in other temples and ends up being a discussion of the place of animal sacrifice in Hinduism and in modern Nepal.